EFEKTIVITAS INOKULAN BRADYRHIZOBIUM DAN GALUR MUTAN KEDELAI TERHADAP KANDUNGAN N DAN HASIL DI LAHAN MASAM - S Gandanegara; J Wemay; Idawati Idawati; Wayan Sabe Ardjasa (Research Center for Biology-Indonesian Institute of Sciences, 2000)
One field experiment had been conducted at Institute for Research and Agricultural Technology Evaluation at Taman Bogo FieldSta,to screen some Bradyhyzobium inoculants on soybean mutant lines developed for acid soil.Inoculants evaluated were single strain B-22,and its mixed inoculants (B-22+B37), (B-22 + G49), and (B-22+TAL 102) on two soybean mutant lines No.07 and 58,and cv.Wilis as check variety. Plant growth and N yield were determined at pod development (R4) and grain maturity (R8) stages.The effect of inoculation significantly influenced nodul-ation and N yield and tended to increase plant dry weight 25%.Mixed inoculant (B-22+B-37) showed good symbiotic compatibility with the three soybean genotypes tested,whereas inoculant(B- 22+G49) only showed good compatibility with mutant line No.58.Cultivar Wilis had broader symbiotic spectrum as compared to mutant line No. 07 and 58.The effect of plant genotypes,and its interaction with inoculants were significant on grain and N yield.It was observed that at pod development stage,the plant growth of mutant line No. 07 were slower than the other genotypes but it had better nutrient translocation rate to grain which resulted grain yield of cv. Wilis. The results showed that this mutant line could be developed for this area.